Specially protected prisoners. Law and practice, or the social consequences of political decision (Archives of Criminology, 2023)
One consequence of the amendment to the Executive Penal Code from 5 January 2011 was the status of a specially protected prisoner. Tis study is based on research aimed at determining the individual and systemic consequences of creating this new category of prisoners. I assumed that these consequences in both aspects would be negative and this assumption was fully confrmed by the empirical material. Te research took place from 2014 to 2017 and consisted of 3 elements: a detailed description of the legislative process, an analysis of statutory, and executive provisions and  an examination of prison practice, whereby interviews were conducted with individuals covered by special protection. Te interviews reveal that these people are treated no diﬀerently than those who pose a serious threat to the safety of others and to order in the prison (so-called “N” prisoners) .